Automation, Trade Unions and Atypical Employment - Piotr Lewandowski; Wojciech Szymczak (Institute of Labor Economics (IZA), 2024)
We study the effect of the adoption of automation technologies – industrial robots, and software and databases – on the incidence of atypical employment in 13 EU countries between 2006 and 2018. We find that industrial robots significantly increase atypical employment share, mostly through involuntary part-time and involuntary fixed-term work. We find no robust effect of software and databases. We also show that the higher trade union density mitigates the robots' impact on atypical employment, while employment protection legislation appears to play no role. Using historical decompositions, we attribute about 1-2 percentage points of atypical employment shares to rising robot exposure.
Keywords: J23; J51; O33; 330; robots; automation; atypical employment; trade unions